The Amazonian shredder caddisfly Phylloicus elektoros Prather, 2003 (Trichoptera: Calamoceratidae): description of the larva and pupa - Campos, Claudimir Menezes; Desidério, Gleison Robson; Martins, Renato Tavares; Hamada, Neusa (Studies on Neotropical Fauna and Environment, 2021)
The Neotropical genus Phylloicus Müller, 1880 has 62 species distributed mainly in Latin America, 27 of which are recorded in Brazil. Larvae of the genus are shredders of organic matter, playing an important role in leaf decomposition in Neotropical streams. They are used in biological and ecological studies. However, only 26% of Phylloicus species have their immature stages described. In order to increase taxonomic knowledge of this genus, we describe and illustrate the larva and pupa of Phylloicus elektoros Prather, 2003. Association of adults of this species with their immature stages was performed through rearing larvae and pupae under laboratory conditions and using the metamorphotype method. The case of P. elektoros has 10–13 leaf fragments. Larvae can be recognized by the reddish-brown color of the head and the hastate-shaped submentum of the genae ventrally. Pupae have almost all of their hook plates with 3–4 pointed, stout hooks. © 2021 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Aquatic insects; Larva